Answer and Explanation:
Given : Expression [tex]5(x-4)+3x-9x+7[/tex]
To find : Use the properties of operations to simplify this algebraic expression. Rewrite the expression by following the directions in each step.
Solution :
Step 1 - Write subtraction as addition,
[tex]=5(x+4)+3x+9x+7[/tex]
Step 2 - Use the distributive property, [tex]a(b+c)=ab+ac[/tex]
[tex]=5x+20+3x+9x+7[/tex]
Step 3 - Use the commutative property of addition to reorder terms so that like terms are together,
[tex]=5x+3x+9x+20+7[/tex]
Step 4 - Use the associative property of addition to group like terms,
[tex]=(5x+3x+9x)+(20+7)[/tex]
Step 5 - Simplify
[tex]=17x+27[/tex]